2017
DOI: 10.12681/bgsg.11139
|View full text |Cite
|
Sign up to set email alerts
|

Development of innovative environmental applications of attapulgite clay

Abstract: In this paper we present a series of laboratory and field, pilot-scale applications of attapulgite clay as an amendment for the stabilization of metals in contaminated soil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Attapulgite can eliminate heavy metals from polluted medium (Samara et al, 2019 ). Zotiadis and Argyraki ( 2017 ) reported that the adsorption efficiency of attapulgite was found to be 100% for Cd, 21% for Ba,100% for As, 100% for Pb, 88% for Zn, and 100% for Sb in a primary schoolyard (Otunola & Ololade, 2020 ). For contaminated solutions, Wang et al ( 2020 ) utilized EDTA-modified attapulgite (EDTA-ATP) for the elimination of aqueous Cr(Ш).…”
Section: Clays and Clay Mineralsmentioning
confidence: 99%
“…Attapulgite can eliminate heavy metals from polluted medium (Samara et al, 2019 ). Zotiadis and Argyraki ( 2017 ) reported that the adsorption efficiency of attapulgite was found to be 100% for Cd, 21% for Ba,100% for As, 100% for Pb, 88% for Zn, and 100% for Sb in a primary schoolyard (Otunola & Ololade, 2020 ). For contaminated solutions, Wang et al ( 2020 ) utilized EDTA-modified attapulgite (EDTA-ATP) for the elimination of aqueous Cr(Ш).…”
Section: Clays and Clay Mineralsmentioning
confidence: 99%
“…Recently, attapulgite (ATP) has attracted attention as a soil amendment 14,15 . ATP is a kind of renewable clay mineral with a layer chain transition structure, which is characterized by a large specific surface area and abundant pores 16,17 . Studies have shown that ATP improved soil water retention capacity, promoted soil structure, adsorbed harmful elements in soil, and reduced the activity and harm of soil pollutants 18 .…”
Section: Introductionmentioning
confidence: 99%
“…14,15 ATP is a kind of renewable clay mineral with a layer chain transition structure, which is characterized by a large specific surface area and abundant pores. 16,17 Studies have shown that ATP improved soil water retention capacity, promoted soil structure, adsorbed harmful elements in soil, and reduced the activity and harm of soil pollutants. 18 ATP also has high mineral nutrients, which increases soil fertility and shows good results in soil remediation, soil improvement, and new fertilizer development.…”
Section: Introductionmentioning
confidence: 99%
“…Attapulgite clay mineral has a high specific surface area and high absorption capacity due to the presence of micropores and parallel channels in the structure 16 . Despite the high absorption properties of attapulgite, it did not receive much attention from researchers as a new type of material in the antiseepage liner.…”
Section: Introductionmentioning
confidence: 99%